Hungarian Monitoring, 3 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation in Karabakh - Central American narcotics mafia has now reached Western Europe Domestic Affairs: - Károly Grósz in Finland - Gyula Horn in Belgrade - Hungarian Socialist Workers' Party (MSZMP) reform circles' general assembly - Events of October 1956 in Esztergom - Persecution of László Tőkés - Csurka makes statement Economy: - Tamás Beck on Hungarian structural transformation and chances of forint convertibility Külpolitika: - Karabahi helyzet - Nyugat-európát is elérte a közép-amerikai kábítószer-maffia Belpolitika: - Grósz Károly Finnországban - Horn Gyula Belgrádban - MSZMP reformkörök nagygyűlés - 1956 októberi történések Esztergomban - Tőkés László üldöztetése - Csurka nyilatkozat Gazdaság: - Beck Tamás a magyar szerkezetátalakításról,ill. a forint konvertibilitásának lehetőségéről